If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 3x + -6 Reorder the terms: 2x = -6 + 3x Solving 2x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2x + -3x = -6 + 3x + -3x Combine like terms: 2x + -3x = -1x -1x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 -1x = -6 + 0 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 0=5x^2-4x-4 | | 9x-15y=10 | | 3/2x+21=0 | | 4(-3)-3y=9 | | n/-9+10=11 | | t^2-245=0 | | 0=2x^2+20x-52 | | 80000.00+209x=249783 | | Y=2x^2+20x-52 | | x^3-7x^2+14x-8=y | | 7/8x-22=27 | | 3(4)-(-2)= | | x^3+4x^2-x-10=y | | 63/3*3*6(6-4) | | 5y-50=4x | | x^3+4x^2-x-10=0 | | 8y-7=14 | | -14=q/3 | | 5(6)+6y=30 | | 24/2*2*5(5-4) | | 45x=-855 | | 0.8x=-8 | | (2-3x)/100 | | y=.5(x-2) | | q+9/3+q-2/2=11/3 | | 3x^6-192=0 | | 3x+30=13x+10 | | 4/3*3*3*4(4-2) | | y+5=-5(x-3) | | y-5=-.66(x+2) | | -3-(8v-5)+(6-7v)-1=7-(v-1)+(4v+4) | | 54/3*3*4(4-2) |